2016
DOI: 10.1093/brain/aww165
|View full text |Cite
|
Sign up to set email alerts
|

George Huntington: a legacy of inquiry, empathy and hope

Abstract: On the centenary of George Huntington's death, Wexler et.al. reconsider the setting and the collaborative effort that produced his description of “hereditary chorea,” today Huntington's disease. Tracing the changing identity of this illness, they discuss the legacy of eugenics, the search for the gene, and ongoing research toward a cure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 39 publications
(35 citation statements)
references
References 12 publications
0
35
0
Order By: Relevance
“…He described its hereditary nature, associated psychiatric and cognitive symptoms and the manifestation of the disease in adult life between 30 and 40 years of age. He outlined the progressive nature of the disease stating, ‘Once it begins it clings to the bitter end’ . However, the monogenic nature and full penetrance of HD makes it perhaps one of the most treatable neurodegenerative diseases.…”
Section: Introductionmentioning
confidence: 99%
“…He described its hereditary nature, associated psychiatric and cognitive symptoms and the manifestation of the disease in adult life between 30 and 40 years of age. He outlined the progressive nature of the disease stating, ‘Once it begins it clings to the bitter end’ . However, the monogenic nature and full penetrance of HD makes it perhaps one of the most treatable neurodegenerative diseases.…”
Section: Introductionmentioning
confidence: 99%
“…HD has a relatively low occurrence: around 10.6-13.7 individuals per 100,000 in western populations, and 1-7 individuals per million in Asian populations [ 7 ]. Even so, George Huntington, the person who first defined the disease in 1872, described it as follows: “Once it begins, it clings to the bitter end” [ 8 ]. There is currently no cure for HD [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…With the antisense oligonucleotide (ASO) huntingtin lowering trial (7) currently underway, there is an urgent need to understand the time course of white matter changes and the mechanisms that drive them so that brain areas can be identified that may benefit from the highest concentrations of ASO.…”
Section: Introductionmentioning
confidence: 99%